Evans, transparency, and Cartesianism. (29th January 2020) - Zapero, David
Abstract: In The Varieties of Reference, Evans makes two parallel claims about thought and perception. He argues that both our capacity to self‐ascribe thought and our capacity to self‐ascribe perception are fallible. The essay focuses on his claim about perception and examines its relation to Evans's project of rejecting a Cartesian conception of the mind. In his theory of perception, I argue, Evans embraces a conception of first‐person authority that he seeks to reject in his account of thought. He is thus not able to extend to perception the critique of Cartesianism that he develops in the context of his analysis of thought. My intent is not exclusively critical. By working through the difficulties that Evans's argument raises, I seek to shed light on whether and, if so, how criticisms of a Cartesian conception of thought may be extended to the philosophy of perception.